1972
DOI: 10.1037/h0033296
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for common and rare words.

Abstract: Two groups of 5s, one exposed to rare and the other to common words, were given three recognition memory lists, each list consisting of 21 targets followed by 21 targets and 21 distractors in random order. The groups were then subdivided for a fourth list such that half of the 5s continued with either rare or common words while the remaining 5s were given items from the other class. The usual finding of superior recognition memory for rare items has observed. The data were interpreted within an interference fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

1974
1974
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 14 publications
3
38
1
Order By: Relevance
“…It should be noted that the present results differ somewhat from those reported by McCormack and Swenson (1972), who found no significant changes in hit rates either within or between lists. The false alarm rates, on the other hand, rose within lists and also increased slightly across lists.…”
Section: Methodscontrasting
confidence: 57%
See 2 more Smart Citations
“…It should be noted that the present results differ somewhat from those reported by McCormack and Swenson (1972), who found no significant changes in hit rates either within or between lists. The false alarm rates, on the other hand, rose within lists and also increased slightly across lists.…”
Section: Methodscontrasting
confidence: 57%
“…Postman, 1971). While LTL in recognition has not been investigated extensively, little or no change in accuracy over successive study-test cycles was found in several experiments, both for categorized lists (Carey & Lockhart, 1973;Connor, 1977;Jacoby, 1973) and for lists of unrelated words (Connor, 1977;McCormack & Swenson, 1972). Divergent effects of practice on performance may represent a potentially important difference between recall and recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This equality, which was observed in both the accuracy and the latency data, has not been demonstrated before. Some investigators have found proactive interference (McCormack & Swenson, 1972;Schulman, 1974;Shepard & Teghtsoonian, 1961); some have failed to find such effects (Donaldson & Murdock, 1968;Shepard & Chang, 1963). Only one study examined both proactive and retroactive interference in recognition (Schulman, 1974).…”
Section: Additional Supporting Resultsmentioning
confidence: 99%
“…lt cannor be ascribed simply to differences in concrereness: Subsets of concrete and abstract words that differed in cue value did not differ in recognition memory. Neither can it be ascribed to differences in ward frequency, which might have been expected to favor the less frequent keywords (McCormack & Swenson, 1972) but which in fact did not. No really satisfactory explanation presents itself, but one possibility, admittedly ad hoc, is that keywords may be "tagged" as words about which decisions have been made.…”
Section: Recognition Memorymentioning
confidence: 99%